2020
DOI: 10.1016/s2214-109x(20)30313-2
|View full text |Cite
|
Sign up to set email alerts
|

Community-based antiretroviral therapy versus standard clinic-based services for HIV in South Africa and Uganda (DO ART): a randomised trial

Abstract: Background Community-based delivery of antiretroviral therapy (ART) for HIV, including ART initiation, clinical and laboratory monitoring, and refills, could reduce barriers to treatment and improve viral suppression, reducing the gap in access to care for individuals who have detectable HIV viral load, including men who are less likely than women to be virally suppressed. We aimed to test the effect of community-based ART delivery on viral suppression among people living with HIV not on ART. Methods We did a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 32 publications
2
142
1
6
Order By: Relevance
“…Equity in access: Three articles highlighted inequity in access to services during COVID-19 times and reinforced the need for additional mechanisms to improve coverage of health services such as supplemental immunisation, catch-up campaigns, home delivery of medicines and mobile van clinics at remote places for poor and marginalised groups (Barnabas et al, 2020; Govender et al, 2020; Wang & Tang, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equity in access: Three articles highlighted inequity in access to services during COVID-19 times and reinforced the need for additional mechanisms to improve coverage of health services such as supplemental immunisation, catch-up campaigns, home delivery of medicines and mobile van clinics at remote places for poor and marginalised groups (Barnabas et al, 2020; Govender et al, 2020; Wang & Tang, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…• People centred care: Four articles discussed, more holistic health services provision based on people needs and epidemiology rather than purely disease specific vertical approach with inclusion of mental health services, geriatric and palliative care which are rather neglected areas in India currently (Edward et al, 2020;Lele & Patwardhan, 2020;Marchand et al, 2020;Patricia et al, 2020). • Equity in access: Three articles highlighted inequity in access to services during COVID-19 times and reinforced the need for additional mechanisms to improve coverage of health services such as supplemental immunisation, catch-up campaigns, home delivery of medicines and mobile van clinics at remote places for poor and marginalised groups (Barnabas et al, 2020;Govender et al, 2020;Wang & Tang, 2020). • Patient and family engagement hold the key: Five articles demonstrated, the importance of empowering patients using health literacy programmes including, behavioural change communication strategies, patient groups involvement in development of service delivery policies and strategies and IT/mobile based grievance reprisal system (Daniel et al, 2020;Elwyn & Price, 2020;Johari et al, 2020;Kuriakose et al, 2020;McCarron et al, 2020).…”
Section: Improving Service Delivery Quality and Safetymentioning
confidence: 99%
“… 12 , 30 In South Africa, a randomised trial on community-based ART initiation and refills delivered by nurses and supervised lay counsellors showed superior viral suppression (74%) compared with clinic-based services (63%). 31 In central Asia, the implementation of home-based HIV care delivery by nurses between 2015 and 2016 increased the number of patients engaged in HIV care by 33% and on ART by 48%. 32 In recognition of successful nurse-led and community-based HIV prevention, care, and treatment delivery models, the US President's Emergency Plan for AIDS Relief advocates adopting rural community-based practical training for nurses in countries with high HIV prevalence.…”
Section: Nursing Contributions To the Hiv/aids Pandemic Responsementioning
confidence: 99%
“…A meta-analysis found that community health worker HIV care delivery signi cantly improved HIV viral suppression, which also reduces sexual transmission (pooled OR: 1.40 95% CI 1.06-1.86) [9]. The DOART trial showed that community-based care was superior to facility-based HIV treatment in supressing HIV viral load [10]. Community-based approaches -particularly when integrated with psychosocial care -can foster social networks, mobilise HIV competent communities and stimulate progress towards the sustainable development goals [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%